Serum Procalcitonin Level is a Useful Predictor of Dilating Vesicoureteral Refl ux in Patients with First Febrile Urinary Tract Infection - Sherein Abdelhamid Shalaby; Mohamed Fathelbab Elsayed (Archives of Clinical Nephrology - Peertechz Publications, 2017)
Background: Procalcitonin (PCT) has been proposed as a novel biomarker for prediction of Vesicoureteral Refl ux (VUR). Since VUR is the most important risk factor for occurrence of pyelonephritis and renal tissue infl ammation, serum PCT level may have a relationship with VUR. However, literature about the relationship between procalcitonin level and VUR is scanty. Aim: We evaluated the predictive value of serum PCT level in the diagnosis of VUR in children admitted with their fi rst febrile UTI. Methods: We investigated 140 children with the fi rst febrile UTI (2m-10 yrs.). Serum PCT was measured before initiation of antibiotics. Standard voiding cystourethrography (VCUG) was performed in all children as the gold standard for detection of VUR. Sensitivity and specifi city of a high PCT level was evaluated using the receiver operating characteristic curve. Results: Seventy three patients(52%) had no VUR, while 67patients (48%) had VUR at least in one kidney, including grade 1 to 2 in 20 patients (14.3%) and , grade 3-5 in 47 (34.7%). PCT level ranged from 0.45 ng/ml to 12.7 ng/ml and, was signifi cantly higher with increasing the grading of VUR. Comparing procalcitonin levels with VCUG results, a sensitivity of 94% and a specifi city of 72% was obtained at a procalcitonin level of 0.52 ng/ml for diagnosis dilating VUR. There was a signifi cant correlation between PCT level and C-reactive protein. Conclusion: This study described that the PCT as an infl ammatory marker with proper sensitivity, specifi city, PPV and NPV seems likely benefi cial to predict dilating VUR.